Implementation of CTL Model to improve Students’ English Learning Achievement - Hanna Pertiwi; Sri Susanti; Eryansyah Eryansyah (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2023)
The objective of this research was to improve students’ learning achievement after being taught using contextual teaching and learning model by using an assessment media conducted online, namely Google Form. This research was conducted at tenth grade students at SMAN 11 Palembang that consisted 35 students in the academic year 2022/2023. This research was collaborative classroom action research with two cycles. The data were collected through Qualitative and Quantitative analysis. Qualitative data were obtained through observations which was carried out during the learning process in the classroom where teacher and students were observed and interviewed to the English teacher after teaching and learning process was completed. In addition, Quantitative data were obtained through tests carried out by students in each learning cycle. The test was in the form of multiple-choice tests. The findings indicated that the implementation of contextual teaching and learning model could improve students’ learning achievement from its average 62,5 in the first cycle to 90,8 in the second cycle. Meanwhile the needs of using technology such as Google Form in the assessment in beneficial factors to support this contextual teaching and learning model.